"Field Study" of the Aryan Movement: In-Class Film and Activity for the Qualitative Methods Course - Keys, Jennifer (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
"Allowed access to national gatherings of U.S. radical right groups including the Ku Klux Klan and the Posse Comitatus, Blood In The Face straightforwardly presents the views of people whose avowed goal is to forge a political union which will transform North America into one Aryan nation. Blatantly and without flinching, members of these groups describe their agenda of anti-Semitism, racism, and extreme nationalism. Their heroes are Adolf Hitler and George Lincoln Rockwell, founder of the American Nazi Party. Wedding ceremonies are performed at burning crosses. Their message is spread through their own home video network." http://www.frif.com/cat97/a-e/blood_in.html